Investigation of possible effect of cemeteries on groundwater - Bomkazi Vava; Abdon Atangana (Journal of Taibah University for Science)
Groundwater, a vital source of fresh water for many, has been negatively impacted by human activities, climate change, and poor management. Human remains from cemeteries can contribute significantly to groundwater pollution if there is a potential connection between the cemetery and the underlying aquifer. This study aimed to assess the impact of cemeteries on groundwater using piecewise differentiation to derive decay models and numerical simulations. The results confirmed observations, and in the unlikely event of a connection between the cemetery and the underlying groundwater, each body could be considered a source of groundwater pollution. The concept of piecewise differentiation was used to provide piecewise advection-dispersion equations, and numerical simulations were presented.